Is the amino acid pattern in medical nutrition therapy crucial for successfully attenuating muscle mass loss in adult ICU patients? Secondary analysis of a RCT. (February 2022) - Dresen, Ellen; Siepmann, Lina; Weißbrich, Carsten; Weinhold, Leonie; Putensen, Christian; Stehle, Peter
Summary: Background and aims: We hypothesized that in long-term immobilized intensive care unit (ICU) patients, both the quantity and quality of protein nutrition are vital in supporting muscle mass maintenance. Hence, the aim of this secondary analysis of our recently performed RCT was to calculate the intake of individual amino acids and to evaluate the potential associations of amino acid patterns with muscle mass loss during the ICU stay. Methods: Clinical and nutritional data were collected from a recent RCT conducted in long-term immobilized, critically ill patients receiving medical nutrition therapy with either 1.8 g (interventional group) or 1.2 g (standard group) of protein/amino acids per kg body weight per day over 4 weeks. Intake of the individual amino acids as well as the sum scores of the indispensable, conditionally indispensable, and dispensable amino acids were calculated for all patients, both group specific (n = 21 in each group) and in total (n = 42), based on the detailed nutrition protocols; inter-group differences were analyzed by t-tests. Linear regression models were used to test the effects of individual amino acids and the sum scores on the extent of skeletal muscle loss by measuring the quadriceps muscle layer thickness during the study period. The significance level was adjusted for multiple testing according to the Bonferroni procedure (α = 0.002). Results: In both groups, the proportion of indispensable amino acids was approximately 41% of the total exogenous protein supply, with the proportion of enteral administration slightly over 50%. The intake of conditionally indispensable amino acids (glutamine, tyrosine, cysteine, histidine, and arginine) accounted for 17% and 18% of the total amino acids in the interventional and standard groups, respectively; glutamine (5% of total amino acids) was exclusively administered enterally. The intake of dispensable amino acid varied widely, with glutamic acid, proline, and asparagine/aspartic acid representing the highest proportions (10%, 8%, and 8% of total amino acids, respectively). For all amino acids, no statistically significant association was observed between the quantitative intake and the skeletal muscle changes after terminating the intervention phase. Conclusion: This secondary analysis of the RCT conducted in routine clinical practice did not support our working hypothesis that the amino acid patterns of medical nutrition therapy have a statistically significant impact on the skeletal muscle loss in long-term immobilized ICU patients. Due to the limited variety of enteral/parenteral products used in this single-center study, the calculated amino acid patterns showed only small differences. Larger multi-center trials with adequate power are needed to evaluate the potential effects of the individual amino acids or defined amino acid patterns on the muscle protein metabolism in further detail. Trial registration: German Clinical Trials Register (http://www.drks.de ); DRKS-ID: DRKS00013594.